Inferior vena cava filters in pregnancy: Safe or sorry? - Bistervels, Ingrid M.; Buchmüller, Andrea; Tardy, Bernard (Frontiers in Cardiovascular Medicine, 2022)
Background Potential hazards of vena cava filters include migration, tilt, perforation, fracture, and in-filter thrombosis. Due to physiological changes during pregnancy, the incidence of these complications might be different in pregnant women. Aim To evaluate the use and safety of inferior vena cava filters in both women who had an inferior vena cava filter inserted during pregnancy, and in women who became pregnant with an inferior vena cava filter in situ. Methods We performed two searches in the literature using the keywords “vena cava filter”, “pregnancy” and “obstetrics”. Results The literature search on women who had a filter inserted during pregnancy yielded 11 articles compiling data on 199 women. At least one filter complication was reported in 33/177 (19%) women and included in-filter thrombosis (n = 14), tilt (n = 6), migration (n = 5), perforation (n = 2), fracture (n = 3), misplacement (n = 1), air embolism (n = 1) and allergic reaction (n = 1). Two (1%) filter complications led to maternal deaths, of which at least one was directly associated with a filter insertion. Filter retrieval failed in 9/149 (6%) women. The search on women who became pregnant with a filter in situ resulted in data on 21 pregnancies in 14 women, of which one (6%) was complicated by uterine trauma, intraperitoneal hemorrhage and fetal death caused by perforation of the inferior vena cava filter. Conclusion The risks of filter complications in pregnancy are comparable to the nonpregnant population, but could lead to fetal or maternal death. Therefore, only in limited situations such as extensive thrombosis with a contraindication for anticoagulants, inferior vena filters should be considered in pregnant women.